Singlet‐Triplet Excited‐State Inversion in Heptazine and Related Molecules: Assessment of TD‐DFT and ab initio Methods. Issue 6 (8th February 2021) - Ricci, G.; San‐Fabián, E.; Olivier, Y.; Sancho‐García, J. C.
Abstract: We have investigated the origin of the S 1 ‐ T 1 energy levels inversion for heptazine, and other N‐doped π ‐conjugated hydrocarbons, leading thus to an unusually negative singlet‐triplet energy gap ( Δ E S T < 0 ). Since this inversion might rely on substantial doubly‐excited configurations to the S 1 and/or T 1 wavefunctions, we have systematically applied multi‐configurational SA‐CASSCF and SC‐NEVPT2 methods, SCS‐corrected CC2 and ADC(2) approaches, and linear‐response TD‐DFT, to analyze if the latter method could also face this challenging issue. We have also extended the study to B‐doped π ‐conjugated systems, to see the effect of chemical composition on the results. For all the systems studied, an intricate interplay between the singlet‐triplet exchange interaction, the influence of doubly‐excited configurations, and the impact of dynamic correlation effects, serves to explain the Δ E S T < 0 values found for most of the compounds, which is not predicted by TD‐DFT. Abstract : Negative gap : Inversion of S 1 and T 1 excited‐states is made possible for N‐ and B‐doped molecules, giving rise to an energy difference ▵ E ST < 0 and thus to exogernic reverse intersystem crossing processes. This inversion is confirmed at CIS(D), SCS‐CC2, SCS‐ADC(2), and SC‐NEVPT2 levels, while TD(A)‐DFT was unable to predict it.